Hubungan Indeks Massa Tubuh, Paritas dan Lama Menopause dengan Densitas Mineral Tulang pada Wanita Pasca Menopause - Fitria, Rahmi (Jurnal Martenity and Neonatal, 2016)
The process of osteoporosis in women after menopause affected by such body mass index ( bmi ), parity and menopausal old.That was increasing every year, it because estogen not, resulting from the follicle but there is another source of estrogen that are produced by cells of adipose.Activity generated by network is smaller than for estrogen that is generated by a follicles and adalagi other factors reduce employment osteoblast.The process of osteoporosis be known by measuring its Bone Mineral Density (BMD).The purpose of research to know the relationship BMI, pariyy and long menopause with BMD women after menopause.The research method was observasional design. Sample wasobtained using random sampling there are 91 women period in Posyandu elderly Rambah Tengah Hilir village, Rambah, Rokan Hulu district, Riau. BMI measurement normal (18.5-24.9 kg/m2) and obesity I (30-34.5 kg/m2) interview to parity and menopause period. The BMD inspection using Quantitative Ultrasound technique (QUS) at heel bone, test result in the from of T scores osteopenia ( -1 SD – -2.5 SD), and osteoporosis (< -2.5 SD).The research result is the correlation BMI and BMD acquire p=0.011, and the correlation menopause period and BMD at women menopause period acquire p=0.000, the correlation parity and BMD women menopause period acquire p=0.719.